Regional patterns of genetic variants in expanded carrier screening: a next-generation sequencing pilot study in Fujian Province, China - Guo, Danhua; Zhou, Nani; He, Qianqian; Lin, Na; He, Shuqiong; He, Deqin; Dai, Yifang; Li, Ying; Chen, Xuemei; Huang, Hailong; Jia, Jia; Cao, Hua; et al. (Frontiers in Genetics, 2025)
BackgroundThis pilot study aimed to characterize the regional distribution of genetic variants associated with autosomal recessive and X-linked recessive (AR/XLR) conditions in Fujian Province, Southeast China, to inform the development of targeted carrier screening programs.MethodsAn expanded carrier screening (ECS) panel utilizing next-generation sequencing (NGS) technology was designed to analyze 332 genes associated with 343 AR/XLR conditions. The panel was applied to 440 samples obtained from individuals in Fujian Province. Single nucleotide variants and copy number variations (CNVs) were identified and analyzed using a multidimensional approach that incorporated demographic characteristics, carrier frequencies, and the genetic burden of AR/XLR diseases.ResultsA total of 511 variants were detected among the 440 participants, including 43 CNVs (8.41%), affecting 133 genes associated with 123 conditions. The mean number of pathogenic or likely pathogenic variants per sample was 1.16. The highest genetic burden was observed in couples seeking medically assisted reproduction (MAR group), who had histories of fetal loss, second- or third-trimester abnormalities, or postnatal abnormalities. In clinical settings, the percentage of at-risk couples (ARCs) was 6.36% (n = 14), involving seven conditions, with no statistically significant difference in ARC incidence between couples undergoing genetic screening (GS group) and the MAR group. The cumulative carrier rate for 28 genes was ≥1/100. Recurrent variants in GAA, GALT, CYP1B1, and MEFV were identified, exhibiting distinct regional patterns compared to previously reported variants in the Han Chinese population.ConclusionNGS-based ECS demonstrates significant potential for assessing the genetic burden of AR/XLR conditions and identifying ARCs in Fujian Province. However, before integrating ECS into regional public health initiatives, the development of a region-specific, curated disease panel is necessary to optimize screening efficacy and clinical utility.